Dampak Agreement On Agriculture Terhadap Ketahanan Pangan Indonesia : Kasus Komoditas Gula (2009 – 2014) - Dimitria Ariesta Pranoto; Asep Saepudin, S.IP, M.Si ; Anik Yuniarti, S.IP, M.Si (Jurnal Paradigma, 2015)
Indonesia’s participation as a member of the World Trade Organization (WTO), brings Indonesia implement the Agreement Establishing the World Trade Organization. In the WTO there are sub topics that regulate agricultural trade, namely the Agreement on Agriculture (AoA). AoA implementation in Indonesia has positive and negative impacts on food security in the case of sugar commodity in Indonesia. This thesis approaches the international regime theory to explain the AoA impact on food security in the case of Indonesian sugar commodities in 2009 - 2014. The aim of this paper is to explain how the AoA impact on food security in the case of Indonesian sugar commodities in 2009 - 2014. The positive impact and negative impacts arise from the application of AoA’s clauses, i.e. market access, domestic subsidies (domestic support) and export subsidies, into the domestic policies related to food security and sugars.